PITUITARY MACROADENOMA MIMICRY: A CASE REPORT - AS, Nurqystina; S, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Nasal polyps causing compression to the pituitary fossa, increased intracranial pressure and ocular nerve palsies are rare. A prompt investigation to exclude pituitary insufficiency is mandatory to prevent a debilitating outcome. CASE Initial pituitary hormone panels demonstrated eupituitarism: morning cortisol 462 nmol/L (NR 102–535 nmol/L), FSH 4.25 IU/ml (NR 3.5–12.5 IU/ml), LH 2.75 mu/ml (2.4–12.6 IU/ml), free T4 11.24 pmol/L (NR 9–19 pmol/L), TSH 1.42 uIU/ml (NR 0.35–4.9 uIU/ml), and prolactin 306 mU/L (NR 102–535 mU/L). However, prior to surgery, she developed secondary hypothyroidism; free T4 9 pmol/L, TSH 3.69 uIU/ml requiring L-thyroxine at 25 mcg/day. Endoscopic transsphenoidal surgery (ETS) was successfully performed and intraoperatively showed suspicion of Rathke's cleft cyst, which histopathologically was reported as an inflammatory polyp. She required a higher dose of L-thyroxine with a temporary replacement of steroids post-op. Her left eye made a full recovery with no residual mass radiologically, but she sustained permanent hypothyroidism. CONCLUSION Nasal polyps uncommonly lead to ocular nerve palsies. Nevertheless, a huge polyp may resemble a pituitary macroadenoma in terms of biochemical investigation and imaging due to its compressive effect, making a histopathological finding a crucial differentiating tool.